Crystal structure of the bis((E)-O-ethyl-N-phenylthiocarbamate) – 4,4′-bipyridine co-crystal (2/1), C28H30N4O2S2 - Yeo, Chien Ing *; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C12H11N5, monoclinic, P21/n (no. 14), a=7.3455(1) Å, b=12.2470(1) Å, c=12.1689(1) Å, β=103.505(1)°, V =1064.45(2) Å3, Z =4, Rgt(F)=0.0365, wRref(F2)=0.0987, T =100 K.